Boswellic acids reduce Th17 differentiation via blockade of IL‐1β‐mediated IRAK1 signaling. Issue 4 (16th February 2014) - Stürner, Klarissa Hanja; Verse, Nina; Yousef, Sara; Martin, Roland; Sospedra, Mireia
<x xml:space="preserve">Abstract</x> Interferon‐gamma producing CD4+ T (Th1) cells and IL‐17‐producing CD4+ T (Th17) cells are involved in the pathogenesis of several autoimmune diseases including multiple sclerosis. Therefore, the development of treatment strategies controlling the generation and expansion of these effector cells is of high interest. Frankincense, the resin from trees of the genus Boswellia, and particularly its prominent bioactive compound acetyl‐11‐keto‐β‐boswellic acid (AKBA), have potent anti‐inflammatory properties. Here, we demonstrate that AKBA is able to reduce the differentiation of human CD4+ T cells to Th17 cells, while slightly increasing Th2‐ and Treg‐cell differentiation. Furthermore, AKBA reduces the IL‐1β‐triggered IL‐17A release of memory Th17 cells. AKBA may affect IL‐1β signaling by preventing IL‐1 receptor‐associated kinase 1 phosphorylation and subsequently decreasing STAT3 phosphorylation at Ser727, which is required for Th17‐cell differentiation. The effects of AKBA on Th17 differentiation and IL‐17A release make the compound a good candidate for potential treatment of Th17‐driven diseases.